2018
DOI: 10.3390/v10020089
|View full text |Cite
|
Sign up to set email alerts
|

The Alphavirus Exit Pathway: What We Know and What We Wish We Knew

Abstract: Alphaviruses are enveloped positive sense RNA viruses and include serious human pathogens, such as the encephalitic alphaviruses and Chikungunya virus. Alphaviruses are transmitted to humans primarily by mosquito vectors and include species that are classified as emerging pathogens. Alphaviruses assemble highly organized, spherical particles that bud from the plasma membrane. In this review, we discuss what is known about the alphavirus exit pathway during a cellular infection. We describe the viral protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 169 publications
2
44
0
Order By: Relevance
“…This finding indicated that prodrug entry into cells is requisite for anti-viral efficacy. The cell lysate also showed a drug concentration-dependent decline in Gag accumulation in samples treated with the prodrug (lanes 2-4) but not in the samples treated with the pre-activated mixture (lanes [6][7][8]. The diminished intracellular Gag accumulation in cells exposed to the prodrug was reported previously and found to reflect Gag mis-sorting to degradative compartments 3 .…”
Section: Resultssupporting
confidence: 73%
“…This finding indicated that prodrug entry into cells is requisite for anti-viral efficacy. The cell lysate also showed a drug concentration-dependent decline in Gag accumulation in samples treated with the prodrug (lanes 2-4) but not in the samples treated with the pre-activated mixture (lanes [6][7][8]. The diminished intracellular Gag accumulation in cells exposed to the prodrug was reported previously and found to reflect Gag mis-sorting to degradative compartments 3 .…”
Section: Resultssupporting
confidence: 73%
“…NiV (31), IAV (32), and EBOV (33) are thought to derive their envelopes from lipid rafts of the plasma membrane, which could specify their lipid content and thus surfactin sensitivity. Alphaviruses such as CHIKV, Mayaro, and Una also bud from the plasma membrane, although neither the lipid content nor the involvement of lipid rafts has been explored (34). Together, these observations suggest that the lipid content of enveloped viruses may explain their differential sensitivity to surfactin.…”
Section: Discussionmentioning
confidence: 97%
“…CHIKV capsid contains two functional domains: the highly positively charged N-terminal RNA binding domain and the C-terminal serine protease domain (44). Following self-cleavage from the nascent structural polyprotein, the capsid protein specifically interacts with the replicated genomic RNA (49S RNA) to form NCs in the cytoplasm (45). The NCs are then transported to the plasma membrane, where they interact with envelope proteins to drive the budding of virus particles from the plasma membrane (46).…”
Section: Resultsmentioning
confidence: 99%